INOVASI MEDIA DIGITAL TANGGITA : TRANSFORMASI PERMAINAN ULAR TANGGA BERBASIS CANVA DAN POWER POINT INTERACTIVE UNTUK PENGUATAN EDUKASI ANTI-BULLYING - Wuli Oktiningrum; Lutfiatus Zuhroh; Adzimatnur Muslihasari; Andi Wibowo (STKIP Persada Khatulistiwa Sintang, 2025)
This study develops and evaluates TANGGITA (Tangga Digital Interaktif), a digital-assisted learning media that transforms the traditional game of Snakes and Ladders into a modernized instructional tool. Developed using Canva and PowerPoint, the media integrates anti-bullying elements and Indonesian cultural diversity content to enhance elementary students’ cultural and civic literacy. Employing the ADDIE development model, the research involved 10 sixth-grade students for small-group trials and 28 fifth-grade students for field testing. Data were collected through expert validation, observations, interviews, tests, and questionnaires. The results show that TANGGITA demonstrated strong validity, with expert scores exceeding 85%. Students’ learning outcomes improved substantially, as reflected in the increase from an average pre-test score of 60.0 to a post-test score of 89,5. The N-Gain value of 0.856, categorized as high, confirms the effectiveness of the media in strengthening students’ understanding of cultural diversity and bullying prevention. The findings indicate that the transformation of traditional games into interactive digital platforms like TANGGITA offers a culturally responsive instructional approach that promotes both cognitive development and positive social behavior in elementary education.